Marriage Legal Aspects On The Status Of Out Of Marriage Children In Birth Certificates And Child Protection - Daud Munasto; Oci Senjaya (LEGAL BRIEF, 2022)
Children are buds, potentials, and the younger generation as the successor to the ideals of the nation's struggle that has a strategic role. Children have special characteristics and characteristics that ensure the continuity of the existence of the nation and state in the future. Children are the living messages we send to a time we will not see (children are the living messages we send for a time we don't see), that's how John W Whitehead in Lenny N. Rosalin describes the importance of children as the next generation as well as the greatest asset for the future. front. Every newly born child must be registered immediately in the form of a Birth Certificate as the child's identity even though the child's status is out of wedlock without losing the rights of the child. This study uses a normative juridical method that is descriptive in nature, which is a systematic and comprehensive description of the object under study. The legal materials used are secondary data consisting of primary, secondary and tertiary legal materials. This research is a library research (library research). To obtain the data presented in this study, the authors used the legal materials obtained were analyzed qualitatively normatively and explained deductively. So that in the end get the expected results, to then draw a conclusion as the final result of this research. The conclusion of this thesis is that the Constitutional Court Decision No. 46/PUU-VIII/2010 which states that Article 43 paragraph (1) of Law Number 1 of 1974 concerning Marriage, namely: "Children born outside of marriage only have a civil relationship with the mother and her mother's family, contrary to the Constitution of the Republic of Indonesia Number 1 of 1945 if it is interpreted as eliminating civil relations with men which can be proven based on science and technology or other evidence according to the law, it is proven that they have blood relations with their fathers. When doing a relationship, it should be considered in the long term, which ultimately does not harm other people, both juridically and non-juridically. Keywords: Child Out of Wedlock, Child Position, Child Protection ABSTRAK Anak merupakan tunas, potensi, serta generasi muda sebagai penerus cita-cita perjuangan bangsa yang memiliki peran strategis. Anak mempunyai ciri dan sifat khusus yang menjamin kelangsungan eksistensi bangsa dan negara pada masa depan. Children are the living messages we send to a time we will not see (anak adalah pesan hidup yang kita kirim untuk masa yang tidak kita lihat), begitulah John W Whitehead dalam Lenny N. Rosalin menggambarkan pentingnya anak sebagai generasi penerus sekaligus aset terbesar untuk masa depan. Setiap anak yang baru dilahirkan untuk segera didaftarkan dalam bentuk Akta Kelahiran sebagai identitas diri anak walaupun status anak luar kawin tanpa menghilangkan hak-hak anak tersebut. Penelitian ini menggunakan metode yuridis normatif yang bersifat deskriptif yaitu mendeskripsikan secara sistematis dan menyeluruh dari obyek yang diteliti. Bahan hukum yang digunakan adalah data sekunder yang terdiri dari bahan hukum primer, sekunder dan terseier. Penelitian ini merupakan penelitian kepustakaan (library research). Untuk memperoleh datadata yang dipaparkan dalam penelitian ini, penulis menggunakan bahan hukum yang diperoleh dianalisis secara kualitatif normatif dan dijelaskan secara deduktif. Sehingga pada akhirnya mendapatkan hasil yang dharapkan, untuk kemudian diambil suatu kesimpulan sebagai hasil akhir dari penilitian ini. Kesimpulan dari skripsi ini adalah dijelaskan Putusan Mahkamah Konstitusi No. 46/PUU-VIII/2010 yang menyebutkan bahwa Pasal 43 ayat (1) Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan yaitu: “anak yang dilahirkan di luar perkawinan hanya memiliki hubungan perdata dengan ibu dan keluarga ibunya, bertentangan dengan UndangUndang Dasar NKRI Nomor 1 Tahun 1945 apabila dimaknai menghilangkan hubungan perdata dengan laki-laki yang dapat dibuktikan berdasarkan ilmu pengetahuan dan teknologi atau alat bukti lain menurut hukum terbukti mempunyai hubungan darah dengan ayahny”. Hendaknya ketika melakukan suatu hubungan harus dipikirkan dalam jangka panjang yang akhirnya tidak merugikan orang lain dalam yuridis maupun non yuridis. Kata Kunci: Anak Luar Kawin, Kedudukan Anak, Perlindungan Anak